Gamification, control and resistance in the delivery app courier sector in Brazil: the iFood case - Ricardo Colturato Festi (Sociología del Trabajo, 2025)
This paper is intended to clarify the new forms of labor organization and resistance on the part of digital platform workers, particularly delivery app motorcyclists in Brasília, the Federal District of Brazil. We will attempt to show relations between structuring a category of motorcycle couriers – characterized by heterogeneity and fragmentation – and the difficulties of putting collective and unity actions together. We will therefore indicate the strategies for political fight and negotiation of their demands with the companies and the State. We will also indicate relations between the obstacles to their organization and the flexible workforce management strategies implemented by digital companies, in particular the modality known as iFood's Logistics Operator. This paper is grounded on data secured from empirical research, particularly semi-structured interviews with Summary